Wpływ integracji z Unią Europejską na funkcję ustawodawczą Sejmu RP: [The influence of the integration with the European Union on the legislative function of the Seym of the Republic of Poland] (Studia Prawnicze / The Legal Studies, 2006)
Akcesja Rzeczypospolitej Polskiej do Unii Europejskiej w dniu 1 maja 2004 r. jest ukoronowaniem wieloletniego procesu integrowania się Polski ze strukturami europejskimi, który przyniósł szereg istotnych konsekwencji społecznych, ekonomicznych, politycznych i prawnych. Widoczne sąjego skutki dla wielu obszarów polskiej państwowości, m.in. w sferze funkcjonowania administracji państwowej. Nieprzypadkowo więc nauka prawa, w tym również prawa konstytucyjnego, poświęca temu zagadnieniu wiele uwagi. Do istotnych nurtów tych badań należąte, które podejmują problematykę konsekwencji integracji europejskiej dla działalności parlamentów narodowych, a w szczególności dla funkcjonowania polskiego parlamentaryzmu. Wśród tych zagadnień godne analizy są konsekwencje tego procesu dla funkcji ustawodawczej Sejmu.  The accession of the Republic of Poland to the European Union (1 May 2004) brought several consequences in social, economical, political and legal fields. One ofthe most important area is functioning ofthe national parliament. With the accession, national parliament has lost approximately 2/3 ofits legislative competences (80% in economical field) to the organs ofthe European Union.The author has analyzed consequences ofthis situation for the legislative function ofthe Seym (lower house ofthe Polish Parliament). He stressed that legislative function was really limited, but at that same time Seym has got new competences in the area ofcontrolling ofthe process ofcreation oflaw of EU. It may be called as a function ofcontrolling ofCommunity's decision-making process in the field ofcreation oflaw. Such an activity is not typical exposure oflegislative function (devoted to creation oflaw), but it is not also typical controlling function (devoted to controlling executive brunch but not in the field ofcreation oflaw). So the author proposes the conception ofa new function ofthe Seym which combine both ofthose activities: the function ofcreation oflaw and opinion-making of the projects oflaw ofthe European Union. In such a formula is was noted that typical legislative function was really changed, but in that same time the parliament receive new competences in the area ofcreation ofthe law but not exactly of the legislative nature. The new opinion-making competences may be treated as kind of the compensation for loosing majority ofthe legislative competences by the Seym. It is very important for national parliament to be appropriately prepared to perform this opinion-making activity while the Committee ofMinisters presents to it the positions on the projects oflaw received from the European Commission. The Seym should posses alternative sources of information and knowledge on European issues to effectively check the positions offered by the Committee of Ministers in a short time available to prepare an opinion. This activity ofparliament may contribute, ifperformed effectively, to limit "the democratic deficit" which may be observed in the activity ofthe European Union. One of the important ways to limit this deficit is the strengthening the role ofnational parliaments, as well as the European Parliament, in the decision-making and opinion-making processes within the UE.